A description of a new species of Typhlotanais (Crustacea: Tanaidacea) from West Antarctic with a note on the genus - Błazewicz-Paszkowycz, Magdalena (Zootaxa, 2004)
The male and female of Typhlotanais grahami n. sp., from shallow waters (2 120 m) in Admiralty Bay (South Shetland Islands, the Antarctic) are described. The revision of Typhlotanais sensu lato is currently underway, and there are enough shared characters to place the new species in the same genus. The female of the new species is characterized by (1) a smooth carapace, as long as it is wide; (2) pereonites smoothly rounded laterally; (3) a rounded pleotelson; (4) an undulated, smooth, spineless mandible molar process; (5) nine terminal spiniform setae (two are fused together) on the maxillule; (6) a chela (propodus) of similar size to the carpus, and twice as long as it is wide; (7) a reduced proximal seta on the pleopodal endopod; (8) a uropod exopodite with one article, about 2/3 of the endopodal length, which is longer distally with a large basal part and a bend about a quarter of the way along its length.